Nicotinamide Adenine Dinucleotide-Dependent Flavin Oxidoreductase of Mycoplasma hyopneumoniae Functions as a Potential Novel Virulence Factor and Not Only as a Metabolic Enzyme - Xie, Xing; Hao, Fei; Chen, Rong; Wang, Jingjing; Wei, Yanna; Liu, Jin; Wang, Haiyan; Zhang, Zhenzhen; Bai, Yun; Shao, Guoqing; Xiong, Qiyan; Feng, Zhixin (Frontiers in Microbiology, 2021)
Mycoplasma hyopneumoniae (Mhp) is the main pathogen that causes enzootic pneumonia, a disease that has a significant impact on the pig industry worldwide. The pathogenesis of enzootic pneumonia, especially possible virulence factors of Mhp, has still not been fully elucidated. The transcriptomic and proteomic analyses of different Mhp strains reported in the literature have revealed differences in virulence, and differences in RNA transcription levels between high- and low-virulence strains initially indicated that nicotinamide adenine dinucleotide (NADH)-dependent flavin oxidoreductase (NFOR) was related to Mhp pathogenicity. Prokaryotic expression and purification of the NFOR protein from Mhp were performed, a rabbit-derived polyclonal antibody against NFOR was prepared, and multiple sequence alignment and evolutionary analyses of Mhp NFOR were performed. For the first time, it was found that the NFOR protein was conserved among all Mhp strains, and NFOR was localized to the cell surface and could adhere to immortalized porcine bronchial epithelial cells (hTERT-PBECs). Adhesion to hTERT-PBECs could be specifically inhibited by an anti-NFOR polyclonal antibody, and the rates of adhesion to both high- and low-virulence strains, 168 and 168L, significantly decreased by more than 40%. Moreover, Mhp NFOR not only recognized and interacted with host fibronectin and plasminogen but also induced cellular oxidative stress and apoptosis in hTERT-PBECs. The release of lactate dehydrogenase by hTERT-PBECs incubated with Mhp NFOR was significantly positively correlated with the virulence of Mhp. Overall, in addition to being a metabolic enzyme related to oxidative stress, NFOR may also function as a potential novel virulence factor of Mhp, thus contributing to the pathogenesis of Mhp; these findings provide new ideas and theoretical support for studying the pathogenic mechanisms of other mycoplasmas.